Impact of infection with extended-spectrum β-lactamase-producing Escherichia coli or Klebsiella species on outcome and hospitalization costs. Issue 1 (January 2016) - Maslikowska, J.A.; Walker, S.A.N.; Elligsen, M.; Mittmann, N.; Palmay, L.; Daneman, N.; Simor, A.
Summary: Background: Extended-spectrum β-lactamase (ESBL)-producing bacteria are important sources of infection; however, Canadian data evaluating the impact of ESBL-associated infection are lacking. Aim: To determine whether patients infected with ESBL-producing Escherichia coli or Klebsiella species (ESBL-EcKs) exhibit differences in clinical outcome, microbiological outcome, mortality, and/or hospital resource use compared to patients infected with non-ESBL-producing strains. Methods: A retrospective case–control study of 75 case patients with ESBL-EcKs matched to controls infected with non-ESBL-EcKs who were hospitalized from June 2010 to April 2013 was conducted. Patient-level cost data were provided by the institution's business office. Clinical data were collected using the electronic databases and paper charts. Findings: Median infection-related hospitalization costs per patient were greater for cases than controls (C$10, 507 vs C$7, 882; median difference: C$3, 416; P  = 0.04). The primary driver of increased costs was prolonged infection-related hospital length of stay (8 vs 6 days; P  = 0.02) with patient location (ward, ICU) and indirect care costs (including costs associated with infection prevention and control) as the leading cost categories. Cases were more likely to experience clinical failure (25% vs 11%; P  = 0.03), with a higher all-cause mortality (17% vs 5%; P  = 0.04). Less than half of case patients were prescribed appropriate empiric antimicrobial therapy, whereas controls received adequate initial treatment in nearly all circumstances (48% vs 96%; P  < 0.01). Conclusion: Patients with infection caused by ESBL-EcKs are at increased risk for clinical failure and mortality, with additional cost to the Canadian healthcare system of C$3, 416 per patient.